Stress, cognitive-emotional regulation, coping, and health in Colombian university students (2021)
During the undergraduate years, there are challenges that students must cope with, in order to achieve academic success and maintain good health throughout their studies. This is a non-experimental, cross-sectional, and correlational research which seeks to explore the relation between stress, cognitive-emotional regulation, coping with university life, and health in 555 Colombian university students aged 16 to 49 years. The results show average and high scores on all variables except physical activity. Also, statistically significant relationships between all variables were verified, which leads to the conclusion that the use of positive cognitive-emotional regulation strategies, low levels of stress, and responses tostress are related to better health, healthy habits, and coping with university life. Based on these results, intervention strategies aimed at strengthening cognitive-emotional regulation in stressful situations could be proposed and implemented to ensure better coping with university.